Organising to learn/learning to organise: three case studies on the effects of union-led workplace learning - Warhurst, C; Findlay, P; Thompson, P (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2006)
Commissioned by the TUC, this paper presents original research by the Scottish Centre for Employment Research on union-led workplace learning. The research examines the relationship between learning and trade union organising at the workplace level. It assesses how trade union organising contributes to worker learning and how that learning affects trade union organising. Based on qualitative research of three TUC-selected case studies, the research finds that for employees there can be provided additional learning and training previously absent from their employment. The three types of learning - for personal development, job-related and to enhance employability - were evident and there is evidence that union-led workplace learning can enable a 'jobs escalator'. Learners can also graduate up a 'learning escalator' from learning that is not directly job-related to learning that is. In participating in learning, unions are able to offer an additional service to existing and prospective members, attitudes to unions are positively changed and recruitment is enhanced. Worker participation in learning can act as a graduating experience, providing a 'roles escalator' that encourages members to become ULRs who, in turn, graduate to other union representative positions. The establishment of the ULR role therefore can be supportive rather than at the expense of more traditional union representation. Finally, there is evidence that learning can contribute to improved industrial relations. These benefits were not comprehensive across the case studies and there are issues that need to be recognised.